ENHANCING THE WHITE-WATER RAFTING EXPERIENCE IN CITARIK RIVER, SUKABUMI: A SERVICE BLUEPRINT AND FRAME EXPERIENCE DESIGN APPROACH - Arsyul Salam, Dicky (International Journal of Sustainable Competitiveness on Tourism, 2024)
Rafting has become a popular adventure activity globally, offering an exhilarating experience for thrill-seekers. Indonesia, with its diverse geography and rich cultural heritage, offers numerous rafting opportunities. The current trends in adventure tourism in Sukabumi, Indonesia, are focused on developing river-based special interest tourism (SIT) products, particularly rafting, river tubing, and body rafting, targeting productive age groups in Sukabumi, Jabodetabek, and Bandung Raya areas. Service blueprinting and framed experience design are two distinct approaches used in service design to enhance customer experiences. By integrating these two approaches, service providers can create a more comprehensive and effective service design strategy. Service blueprinting can help identify areas for improvement in the service delivery process, while framed experience design can help create a cohesive and engaging experience by framing the context, atmosphere, and activities that make up the experience (Pandey & Kulshrestha, (2021); Li & Lu, (2021)). Therefore, this study aims to investigate how service blueprints and frame experience design can be applied to enhance the rafting experience, ultimately contributing to the growth and sustainability of the industry. This research will adopt a quantitative technique and data collected will be analyzed using descriptive statistics and Importance-Performance Analysis (IPA) quadrant matrix. The result suggests that while most aspects of the white-water rafting experience are performing well in areas of high importance, there are a few areas where improvement efforts could be focused to increase satisfaction levels, particularly in managing river current conditions, enhancing storytelling and entertainment aspects, and providing more opportunities for self-development.